Variation of social strategies between bluff and unobtrusive immigrant males during integration into a new social group: a case study in Macaca thibetana - Zhao, Cheng-Ren; Chen, Shi-Wang; Tian, Hong-Wei; Sun, Binghua; Zhang, Qi-Xin; Xia, Dong-Po (Frontiers in Ecology and Evolution, 2023)
Immigrant males employed a range of species-specific social strategies to facilitate integration into a new social group for establishing stable dominant ranks and affiliative relationships with unfamiliar competitors who require them to adapt their behavior. However, less is known whether the social strategies of integration were individual-specific. In this study, nine immigrant males provided a natural experiment to investigate the variation of social strategies between the bluff and unobtrusive immigrant males during integration into a new social group. We followed the wild YA1 Tibetan macaque group and collected the behavioral data from August 2021 to May 2022. The results showed that the bluff and unobtrusive immigrant males faced similar social pressure from intrasexual individuals in the target social group during both the prospecting and integrating stages. During the prospecting stage, the bluff and unobtrusive immigrant males formed “attempt strategies” to seek and establish social relationships with unfamiliar individuals in a new group. The bluff immigrant males formed affiliative relationships with high-ranking females and resident males whereas the unobtrusive immigrant males formed affiliative relationships with low-ranking females during the integrating stage. Our results firstly provided quantitative methods to distinguish prospecting and integrating stages during immigration processes. The results also demonstrated that the bluff and unobtrusive immigrant males formed varied social strategies. Our results provided new insight into understanding the individual-specific social strategies of immigrant males during integration into a new social group.